Assessing regulatory changes in the transport sector: An introduction - Lorenzo Casullo; Nathan Zhivov (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
The specific characteristics of transport services and markets, including their importance in socioeconomic terms, are such that Regulatory Impact Analysis (RIA) is particularly likely to yield major benefits when applied to transport policy. However RIA in transport is not as widespread as in other sectors given the presence of some major barriers. This paper explains the aspects of a good practice RIA system for transport regulations. It describes the rationale and the benefits of RIA frameworks and provides advice on dealing with the practical realities of implementing RIA in the transport sector. It concludes with recommendations for governments seeking to implement RIA within their jurisdictions.
Keywords: 330